2018
DOI: 10.1101/473231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A clinal polymorphism in the insulin signaling transcription factorfoxocontributes to life-history adaptation inDrosophila

Abstract: A fundamental aim of adaptation genomics is to identify polymorphisms that underpin variation in fitness traits. In Drosophila melanogaster, latitudinal life-history clines exist on multiple continents and make an excellent system for dissecting the genetics of adaptation. We have previously identified numerous clinal single-nucleotide polymorphism in insulin/insulin-like growth factor signaling (IIS), a pathway known from mutant studies to affect life history. However, the effects of natural variants in this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 188 publications
(308 reference statements)
2
6
0
Order By: Relevance
“…Consistent with predictions, the low latitude flies showed a 12% greater quantity of InR transcript than the high latitude flies. Durmaz et al (2019) conclude that these clinal foxo variants have pleiotropic effects on fitness-related traits that are consistent with trade-offs and contribute to observed life history clines of North American D. melanogaster. Together with similar results on a polymorphism in InR (Paaby et al 2010(Paaby et al , 2014, the results of Durmaz et al (2019) suggest that natural variation in IIS makes an important contribution to clinal adaptation in Drosophila.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with predictions, the low latitude flies showed a 12% greater quantity of InR transcript than the high latitude flies. Durmaz et al (2019) conclude that these clinal foxo variants have pleiotropic effects on fitness-related traits that are consistent with trade-offs and contribute to observed life history clines of North American D. melanogaster. Together with similar results on a polymorphism in InR (Paaby et al 2010(Paaby et al , 2014, the results of Durmaz et al (2019) suggest that natural variation in IIS makes an important contribution to clinal adaptation in Drosophila.…”
supporting
confidence: 67%
“…Studying such natural polymorphisms allow evolutionary geneticists to address key questions such as: "Which genetic mechanisms underlie variation in fitness-related traits?," "What are the * This article corresponds to Durmaz, E., S. Rajpurohit phenotypic effects of natural life-history variants?," and "Do evolutionary changes in life-history traits occur independently, or via the same pathways and genes?" Durmaz et al (2019) identified a natural variant of the foxo gene in D. melanogaster that exhibits a strong allele frequency cline along the North American east coast. This variant consists of two alternative alleles, one of which is common at low latitude (Florida) and the other at high latitude (Maine), with the alleles differing at two nucleotide positions.…”
mentioning
confidence: 99%
“…Similar to ours, these studies found only weak support for an involvement of loci in the IIS/TOR or other major longevity pathways in the evolution of longevity (Table S5). This is an interesting observation given that functional variation in canonical "aging" genes in natural populations has been observed to contribute to life history adaptation along latitudinal clines, for example the Drosophila Insulin receptor (InR) (Paaby et al 2010;Paaby et al 2014), transcription factor foxo (Durmaz et al 2019), and methusaleh (Paaby and Schmidt 2008). However, the selection pressures to which these alleles respond in clinal populations may be different from selection for postponed reproduction or adaptation to larval diet such as in our experiment.…”
Section: Different From 'Canonical' Longevity Genesmentioning
confidence: 68%
“…These sites were observed to be in perfect linkage disequilibrium ( r 2 =1) in the DGRP, such that they covary and are not independent. Further details regarding these polymorphic sites and the landscape of linkage disequilibrium at foxo are provided in our previous publication (Durmaz et al, 2019).…”
Section: Methodsmentioning
confidence: 99%